1999
DOI: 10.1002/vnl.10324
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments: Benzoate esters in polyvinyl resilient flooring

Abstract: Benzoate plasticizers provide excellent foam quality, stain resistance, and UV light stability. They are used as primary plasticizers in resilient flooring applications but are limited in use because of viscosity. New benzoate‐based blends have been developed that result in reduced‐viscosity plastisols and lower VOC emissions than for existing benzoate products. A variety of European and North American formulations have been used to evaluate the processing and performance properties of these benzoate‐based ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is often the phthalate di-ester, di-2-ethylhexyl phthalate (DEHP) (Cadogan et al 1999;Wilson 1995;Ejlertsson et al 1997), but others such as di-2-ethylhexyl adipate (DEHA) are also commonly used (Tepper 1973;Startin et al 1987;Nerin et al 1992;Bohnert et al 1999;Lang and Stanhope 2001). A study in Germany in 2002 found average DEHP levels of 2.27 lg/l in surface waters and 0.70 mg/kg in sediments (Fromme et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…This is often the phthalate di-ester, di-2-ethylhexyl phthalate (DEHP) (Cadogan et al 1999;Wilson 1995;Ejlertsson et al 1997), but others such as di-2-ethylhexyl adipate (DEHA) are also commonly used (Tepper 1973;Startin et al 1987;Nerin et al 1992;Bohnert et al 1999;Lang and Stanhope 2001). A study in Germany in 2002 found average DEHP levels of 2.27 lg/l in surface waters and 0.70 mg/kg in sediments (Fromme et al 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The lubricant treatment improved the friction properties and surface structuring had a great effect on the water contact angle. The common targets of modification of plastic surfaces were to develop new plasticizers and mixtures (Bohnert et al 1998, Puukilainen and Pakkanen 2005, Koponen et al 2007a, and to modify hydrophobic properties (Fresnais et al 2006, Li et al 2006, Puukilainen et al 2006, Koponen et al 2007b) and surface structures (Li et al 2006, Puukilainen et al 2006, Koponen et al 2007b. Surface structure was reported to affect the hydrophobic properties (Fresnais et al 2006, Li et al 2006, Koponen et al 2007b).…”
Section: Plastic Materialsmentioning
confidence: 99%
“…In particular, resilient-flooring plastisols can utilize high solvators for improved processing. In this article, resilient-flooring plastisols will be used to illustrate the performance of high solvators, thus expanding upon earlier work with benzoate ester technology [2,3].…”
Section: Introductionmentioning
confidence: 99%